Kříž u potoka Karolíny Světlé - Všetièka, František (Bohemistyka, 2018)
In her novel Kříž u potoka (1868) Karolína Světlá applied a contrastive principle, which is seen mostly in the relationships between her characters. A part of this principle is represented by vertical space completed by a place of horror (locus horridus). The place of horror is twofold in this novel, the latter is related to the anticipant character (a holy old women). The novel is framed in two ways – in a mortal and a local way. The opening of the novel is represented by Vorgeschichte, while the rest of the story is covered in the superstitious time.